Genome Sequence, Assembly, and Characterization of the Antagonistic Yeast Candida oleophila Used as a Biocontrol Agent Against Post-harvest Diseases - Sui, Yuan; Wisniewski, Michael; Droby, Samir; Piombo, Edoardo; Wu, Xuehong; Yue, Junyang (Frontiers in Microbiology, 2020)
Candida oleophila is an effective biocontrol control used to control postharvest diseases of fruits and vegetables. C. oleophila I-182 was an active agent used in the first-generation of yeast-based commercial product, Aspire™, for postharvest disease management. Several action modes, like competition for nutrients and space, induction of pathogenesis-related genes in host tissues, and production of extracellular lytic enzymes, have been demonstrated for the biological control activity exhibited by C. oleophila through which it inhibits postharvest pathogens. In the present study, the whole genome of C. oleophila I-182 was sequenced using PacBio and Illumina shotgun sequencing technologies, yielding an estimated genome size of 14.73 Mb. The genome size is similar in length to that of the model yeast strain Saccharomyces cerevisiae S288c. Based on the assembled genome, protein-coding sequences were identified and annotated with a gene description. The predicted genes were further assigned with gene ontology (GO) terms and clustered in special functional groups. A comparative analysis of C. oleophila proteome with the proteomes of 11 representative yeasts revealed 2 unique and 124 expanded families of proteins in C. oleophila. Availability of the genome sequence will facilitate a better understanding the properties of biocontrol yeasts at the molecular level.